(untitled) (CIPEEX, 2025)
With the growing advancement of technology and the expansion of distance learning, the private education market has been transformed, offering new opportunities for teachers and students to connect virtually. In this scenario, Learrny has emerged as an innovative digital platform aimed at facilitating the interaction between private teachers and students seeking tutoring in academic and school subjects. The project aims to optimize this connection through a simple and intuitive platform. The MVC (Model-View-Controller) architecture was chosen to organize the development of the software, allowing a clear separation between the presentation logic and the data, which facilitates the maintenance and scalability of the system. The project adopted agile methodologies such as Lean Inception, Scrum and Kanban, integrating concepts from disciplines such as software quality, API development, software architecture, digital processing and computational mathematics, which are fundamental to building the platform and ensuring its robustness and security. The API, which is currently being perfected, will be responsible for effectively managing the flow of data, connecting students and teachers in an agile way. As a result, Learrny is expected to establish itself as a benchmark in private education, fostering an environment that benefits both teachers looking to expand their careers and students in need of personalized academic support.